FORMING OF RESEARCH COMPETENCE OF FUTURE ENGINEERS DURING TEACHING EDUCATIONAL DISCIPLINES OF NATURAL-SCIENCE TRAINING CYCLE - Світлана Бєлкіна (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
In the article it is fulfilled the analysis of models of forming of research competence of students of different profile and pupils. In the structure of research competence of the future engineer it is allocated general-scientific, sectoral and subject level's elements, which can and have to be formed while teaching the cycle of natural-science training. It is recognized, that possession of the scientific methodology of cognition is one of the key elements of future engineer's research competence, which should be formed during the whole period of study in high school, beginning from the first course. It was found that a key condition for forming of research competence of students is organization of their active educational-research activities, which corresponds to the logic and structure of scientific research.